2018
DOI: 10.2147/jpr.s164128
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled Phase III trial of duloxetine in Japanese patients with knee pain due to osteoarthritis

Abstract: PurposeTo examine the efficacy and safety of duloxetine in Japanese patients with knee pain due to osteoarthritis.Patients and methodsPatients were randomized to receive duloxetine 60 mg/day or placebo for 14 weeks in a double-blind manner (ClinicalTrials.gov Identifier: NCT02248480). The primary efficacy endpoint was mean change in Brief Pain Inventory pain severity (BPI-Severity) average pain. Secondary endpoints included improvement in other BPI-Severity scales, Patient Global Impression of Improvement, Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 26 publications
2
67
3
1
Order By: Relevance
“…In addition, duloxetine improved the sensitivity to non‐noxious mechanical stimuli measured by a pain behavioral test in the intervertebral disc‐related radiculopathy model in rats, which is truly regarded as a model for neuropathic pain . With regard to clinical results, several studies conducted in the United States, Europe, and Asia have shown significant improvements in pain, joint junction and function, and health‐related quality of life for patients with hip or knee OA who were treated with duloxetine compared with placebo without serious adverse events . Because duloxetine has been already recommended as the first‐line drug for neuropathic pain based on strong GRADE recommendations for use, our hypothesis that duloxetine is effective for neuropathic pain in OA can be considered reasonable.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In addition, duloxetine improved the sensitivity to non‐noxious mechanical stimuli measured by a pain behavioral test in the intervertebral disc‐related radiculopathy model in rats, which is truly regarded as a model for neuropathic pain . With regard to clinical results, several studies conducted in the United States, Europe, and Asia have shown significant improvements in pain, joint junction and function, and health‐related quality of life for patients with hip or knee OA who were treated with duloxetine compared with placebo without serious adverse events . Because duloxetine has been already recommended as the first‐line drug for neuropathic pain based on strong GRADE recommendations for use, our hypothesis that duloxetine is effective for neuropathic pain in OA can be considered reasonable.…”
Section: Discussionsupporting
confidence: 52%
“…The Osteoarthritis Research Society International (OARSI) guidelines recommend duloxetine as treatment for multiple‐joint OA with or without comorbidities . Some RCTs and meta‐analyses revealed the efficacy and safety of duloxetine for OA pain . Moreover, the SNRIs, including duloxetine, are regarded as the first therapeutic agents for neuropathic pain .…”
mentioning
confidence: 99%
“…With regard to randomisation and allocation concealment, one study 23 showed an unclear risk and the remaining five studies [20][21][22]24,25 all showed a low risk. Furthermore, all six studies appeared to be at low risk with regard to blindness, incomplete outcome data, and selective reporting, but they were unclear for other biases.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…В рандомизированном двойном слепом плацебо-контролируемом исследовании японских ученых оценивались эффективность и безопасность дулоксетина у пациентов с ОА коленных суставов в течение 14 нед. Показано значимое уменьшение боли, скованности, функциональной недостаточности и улучшение качества жизни в группе дулоксетина [34].…”
Section: к л а с с и ф и к а ц и о н н ы е к р и т е р и и оа т а з оunclassified